Application of combined gas chromatography and dielectric spectroscopy in SF6 gas insulated high voltage converter transformer bushing insulation performance. Issue 5 (January 2021) - Gong, Lin; Zhang, Shiling
Abstract: High voltage converter transformer bushing is widely used in the outlet part of high-end converter transformer, and its operation safety and stability directly determine the operation effect of converter transformer. The bushing of SF6 gas insulated high voltage converter transformer is a typical multi-media insulation structure. The air end of the bushing includes SF6 gas insulation medium, and the bushing tail is in contact with transformer oil. The bushing body is generally epoxy impregnated paper composite insulation structure. For the complex insulation system, the running state of converter transformer bushing should be monitored in real time. For gas phase insulation, gas chromatography is generally used to dynamically analyze the composition of SF6 gas; for epoxy impregnated paper solid insulation, dielectric spectrum technology is generally used to analyze its wide frequency domain dielectric characteristics. Therefore, the combination of gas chromatography and dielectric spectroscopy technology can effectively characterize the insulation performance of SF6 gas insulated high-voltage converter bushing. In view of this, this paper first gives the basic theory of frequency domain dielectric spectroscopy technology and gas chromatography technology, and further analyzes the current carrying and heating conditions of the central conductor of high-voltage converter bushing under overload and short-circuit conditions. The dielectric spectrum characteristics of the converter bushing core under different temperature conditions are obtained by experiment, and the Cole-Cole model is used for fitting analysis. The decomposition characteristics of SF6 insulation gas in epoxy resin composite insulator under overload and short-circuit conditions are analyzed experimentally, and the variation curve of SF6 characteristic decomposition gas with time is obtained. Combined with the above relationship between gas chromatography and dielectric spectrum, an operational evaluation strategy for the performance of SF6 gas insulated high voltage converter bushing is proposed. In this paper, for the first time, the internal insulation performance of high-voltage converter bushing is comprehensively evaluated by gas chromatography and dielectric spectrum analysis technology for the first time, which has certain theoretical and practical application value for the operation, maintenance and overhaul of converter bushing.